Planejamento tributário: um estudo pela perspectiva do constructivismo lógico-semântico - Tomé, Giovani Hermínio (2011)
The objective of this study is to highlight the autonomy of law in relation to other matters taken by related. For this, we assumed that the positive law is structured in the form of autonomous system and the elements of this system are expressed by propositions made with hypothetical conditions. It starts by saying a few remarks about the assumptions of Logical Semantic Constructivism to provide a theoretical basis of our studies, demonstrating the structure and function of the language of positive law. In this way, based on the operability of the legal system, we record our conclusions about the scope, limits and possibilities of tax planning in light of the law in force